(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article describes the morphological, biological characteristics of the Bracon hebetor parasite and the effectiveness of its use in the fight against the southern storage moth (Plodia interpunctella) during the storage of agricultural products.